Mass spectrometric quantification of amino acid oxidation products identifies oxidative mechanisms of diabetic end-organ damage - Vivekanadan-Giri, Anuradha (2008)
Diabetes mellitus is increasingly prevalent worldwide. Diabetic individuals are at markedly increased risk for premature death due to cardiovascular disease. Furthermore, substantial morbidity results from microvascular complications which include retinopathy, nephropathy, and neuropathy. Clinical studies involving diabetic patients have suggested that degree of diabetic hyperglycemia correlates with risk of complications. Recent evidence implicates a central role for oxidative stress and vascular inflammation in all forms of insulin resistance, obesity, diabetes and its complications. Although, glucose promotes glycoxidation reactions in vitro and products of glycoxidation and lipoxidation are elevated in plasma and tissue in diabetics, the exact relationships among hyperglycemia, the diabetic state, and oxidative stress are not well-understood. Using a combination of in vitro and in vivo experiments, we have identified amino acid oxidation markers that serve as molecular fingerprints of specific oxidative pathways. Quantification of these products utilizing highly sensitive and specific gas chromatography/mass spectrometry in animal models of diabetic complications and in humans has provided insights in oxidative pathways that result in diabetic complications. Our studies strongly support the hypothesis that unique oxidants are generated in the microenvironment of tissues vulnerable to diabetic damage. Potential therapies interrupting these reactive pathways in target tissue are likely to be beneficial in preventing diabetic complications.